Marketing social en la creación de un centro científico-místico, para potenciar el desarrollo personal integral en Cuenca - Ecuador - Delgado Muñoz, Lupe Cecilia (2024)
Official statistics show worrying figures related to the low response capacity of Ecuadorians to the challenges of today's life. The post-pandemic effects aggravated the situation, given the dizzying changes that the world has faced. It is easy to realize the phenomenon and the social behavior that it has caused in Ecuador; Therefore, it is greatly reflected at the country level in a working society with mental-emotional limits and serious difficulties in making assertive decisions. In this context, the opportunity was identified in Cuenca - Ecuador for the creation of a scientific-mystical center for comprehensive personal development that offers solutions to the management of emotions and knowledge to respond to life's challenges; They are experiential workshops that combine scientific-mystical techniques in face-to-face processes. With the objective of developing social marketing in this project, a survey was first created applied to the economically active potential consumer in the city of Cuenca, in order to identify demographic data such as: tastes, preferences, consumer experience; as well as your ability to pay. Additionally, marketing and communication experts were interviewed to collect data that reinforces what was previously investigated and sheds light on the development of the objective. For this purpose, a deductive method was used, a quantitative approach in a survey questionnaire and an inductive method, a qualitative approach through interviews. The first was carried out in companies, gyms, reading groups, among others; while the second was carried out to marketing and communication professionals. The investigation yielded positive results concluding in the feasibility of the investigated project.